1994
DOI: 10.1175/1520-0477(1994)075<0005:hrsifm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Satellite Imagery for Mesoscale Meteorological Studies

Abstract: In this article high-resolution satellite imagery from a variety of meteorological and environmental satellites is compared. Digital datasets from Geostationary Operational Environmental Satellite (GOES), National Oceanic and Atmospheric Administration (NOAA), Defense Meteorological Satellite Program (DMSP), Landsat, and Satellite Pour I'Observation de la Terre (SPOT) satellites were archived as part of the 1990 Hawaiian Rainband Project (HaRP) and form the basis of the comparisons. During HaRP, GOES geostatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…the observed downwelling solar radiation divided by the calculated clear-sky value) and the Meteosat data, for the visible TOARs and the 11 µm BTs. (Observed errors in the geolocation of the Meteosat data were corrected, and a parallax correction was applied to all pixels (Johnson et al, 1994), using a cloud-top height of 6 km. This height was derived from vertical scans by the high-power radars at Chilbolton.…”
Section: Observed Effects Of the Cirrus Cover On Surface Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…the observed downwelling solar radiation divided by the calculated clear-sky value) and the Meteosat data, for the visible TOARs and the 11 µm BTs. (Observed errors in the geolocation of the Meteosat data were corrected, and a parallax correction was applied to all pixels (Johnson et al, 1994), using a cloud-top height of 6 km. This height was derived from vertical scans by the high-power radars at Chilbolton.…”
Section: Observed Effects Of the Cirrus Cover On Surface Fluxesmentioning
confidence: 99%
“…A parallax correction was applied to the Meteosat data (Johnson et al, 1994). This assumed a cloud-top height of 5 km, since radiosonde data collected in the CSIP area showed that, provided the lid at around 900 hPa could be overcome, convection from the surface could rise to a height of around 550 hPa (approximately 5 km).…”
Section: Analysis Of Observed Convective Initiation In the Csip Areamentioning
confidence: 99%
“…The variation of t off is not only similar to results described already by Johnson et al (1994) for NOAA satellites. It is a characteristic feature of a sun-synchronous orbit.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated e.g. for NOAA-11 satellite that the time offset between ±60 degrees varies not more than ±60 minutes (Johnson et al, 1994). A further advantage consists in very similar conditions of illumination in the same geographic latitude of neighbouring passes within a relatively short time interval, perhaps within the 16 days of LANDSAT repetition rate.…”
Section: Methodsmentioning
confidence: 99%
“…Les satellites défilants employés actuellement en météorologie (Johnson et al, 1994) gravitent sur des orbites situées à environ 850 km d'altitude, passant au voisinage des pôles et synchronisées par rapport au soleil, souvent appelées orbites héliosynchrones quasi polaires. On obtient ainsi pour chaque satellite une couverture de l'ensemble du globe toutes les douze heures.…”
Section: Satellites Géostationnaires Et Défilantsunclassified